Formal aspects of component software : 14th International Conference, FACS 2017, Braga, Portugal, October 10-13, 2017, Proceedings /: 14th International Conference, FACS 2017, Braga, Portugal, October 10-13, 2017, Proceedings. (2017) - Unknown
No abstract available